Kematangan Emosi, Religiusitas Dan Perilaku Prososial Perawat Di Rumah Sakit - Dwi Haryati, Tutik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. The purposes of this study were to determine the relationships between emotional maturity and religiosity with nurses’ prosocial behavior at hospital. Research samples were nurses working at Mother Hospital Surabaya total of 61 people. Data were collected by the scales of emotional maturity, religiosity and prosocial behavior. Studies using multiple regression analysis. Results of research were as follows: First, there was a positive and significant relationship between emotional maturity and religiosity with nurses’ prosocial behavior. Second, there was a positive and significant relationship between the emotional maturity and prosocial behavior of nurses. Third, there was a significant and positive relationship between religiosity and nurses’ prosocial behavior.Keywords: emotional maturity, religiosity and nurse’ prosocial behavior